1986
DOI: 10.1002/1097-0142(19861215)58:12<2697::aid-cncr2820581225>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytic sarcoma in nonleukemic patients

Abstract: Sixteen patients presenting with granulocytic sarcoma without evidence of acute leukemia were seen and diagnosed at The University of Texas M.D. Anderson Hospital and Tumor Institute at Houston from 1962 to 1985. Seven of them (44%) did not develop acute leukemia. Of these seven, four are alive with no evidence of disease 3.5 to 16 years after initial presentation; the remaining three patients died of their disease within 2 to 8 months of presentation. Two of 16 patients were diagnosed within the last 15 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
245
1
8

Year Published

1988
1988
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(258 citation statements)
references
References 48 publications
4
245
1
8
Order By: Relevance
“…On the contrary, 25 (58%) of 42 patients given chemotherapy remained in the nonleukemic stage for more than 11 months. Meis et al 5 reported that at least 4 (25%) of 16 patients who received chemotherapy did not develop ANLL during a follow-up period of 3.5-16 years after diagnosis of GS. Among the cases reviewed here, most misdiagnosed patients were treated with cytotoxic agents used for NHL, sarcoma, or multiple myeloma, and most patients who initially were diagnosed with GS received aggressive chemotherapy coincident with ANLL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, 25 (58%) of 42 patients given chemotherapy remained in the nonleukemic stage for more than 11 months. Meis et al 5 reported that at least 4 (25%) of 16 patients who received chemotherapy did not develop ANLL during a follow-up period of 3.5-16 years after diagnosis of GS. Among the cases reviewed here, most misdiagnosed patients were treated with cytotoxic agents used for NHL, sarcoma, or multiple myeloma, and most patients who initially were diagnosed with GS received aggressive chemotherapy coincident with ANLL.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 On rare occasions, it evolves before the onset of ANLL, and among these cases it often is misdiagnosed as malignant lymphoma. 3,5 We report two patients with GS of left testicular and intestinal involvements, respectively, that preceded leukemic involvement of the peripheral blood and bone marrow. To our knowledge, there has been no previous review comparing treatments for patients with GS in the nonleukemic stage preceding ANLL.…”
mentioning
confidence: 95%
“…Alguns autores relatam intervalos prolongados entre o aparecimento da lesão orbitária e o acometimento sistêmico, variando de 1 a 16 anos (14)(15) .…”
Section: Discussionunclassified
“…In patients with AML, MS is present in 2-8 % of these patients [5]. In adults, the true incidence of MS is unknown, although in roughly one third of cases it may occur concurrently with other myeloid diseases including myelodysplastic syndrome (MDS), myeloproliferative neoplasm (MPN) or MDS/MPN [6][7][8][9][10][11], but such an association is not required. In pediatric AML however, MS occurs in approximately 10 % of cases [11].…”
Section: Diagnosis Myeloid Sarcomamentioning
confidence: 99%